2013
DOI: 10.30843/nzpp.2013.66.5654
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of <i>Venturia inaequalis</i> to demethylation inhibitor and dodine fungicides in four New Zealand applegrowing regions

Abstract: A survey of 41 apple orchards in Hawkes Bay (25) Nelson (7) Otago (4) and Waikato (5) provided 796 isolates of Venturia inaequalis (black spot or scab) which were tested using an agar plate assay for sensitivity to two demethylation inhibitor (DMI) fungicides (myclobutanil and penconazole) and to dodine Each fungicide was used at two concentrations to distinguish between highly sensitive sensitive and resistant isolates Sensitivity to DMIs in all regions was lower than baseline sensitivity in previous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
8
1
Order By: Relevance
“…For example, in Mycosphaerella graminicola, resistant ascospore populations increased from 35 to 80% in wheat plots after the irst QoI application and exceeded 90% after the second QoI application (Fraaije et al 2005). This pattern is quite different from that observed with the DMI fungicides, where there is a continuous range of sensitivities and mean EC 50 shifts gradually towards resistance over a long period of time (Beresford et al 2013).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…For example, in Mycosphaerella graminicola, resistant ascospore populations increased from 35 to 80% in wheat plots after the irst QoI application and exceeded 90% after the second QoI application (Fraaije et al 2005). This pattern is quite different from that observed with the DMI fungicides, where there is a continuous range of sensitivities and mean EC 50 shifts gradually towards resistance over a long period of time (Beresford et al 2013).…”
Section: Discussioncontrasting
confidence: 91%
“…Approximately 20 V. inaequalis isolates per orchard were obtained during December 2011 and January 2012 from apple fruit lesions from 41 orchard blocks in Hawke's Bay (25), Nelson (7), Otago (4) and Waikato (5), as described in Beresford et al (2013). The cultivars sampled were 'Royal Gala' (35), 'Braeburn' (2), 'Fuji' (2) and Pink Lady® (2).…”
Section: Orchard Survey V Inaequalis Isolation and Fungicide Use Inmentioning
confidence: 99%
“…The 1985 New Zealand survey of B. cinerea benzimidazole resistance (Beever et al 1989) found no correlation between benzimidazole use and resistance frequency in individual vineyards. Other more recent New Zealand studies also found no correlation at the individual vineyard or orchard level between fungicide sensitivity and spray diary records for Erysiphe necator in grapes , or for Venturia inaequalis in apples (Beresford et al 2013). There could be several reasons for a lack of correlation between fungicide use and pathogen sensitivity, including: 1) fungicide usage differing little between vineyards over the time frame relevant to resistance selection, 2) migration of pathogen strains between vineyards and 3) sample sizes too small to quantify small differences in sensitivity accurately between individual vineyards.…”
Section: Discussionmentioning
confidence: 88%
“…In the absence of baseline data and genetic testing for beta tubulin mutations, it cannot be ascertained if the carbendazim response is natural or is part of a multidrug resistance development. For example, multidrug resistance of V. inaequalis to demethylation inhibitor and dodine fungicides in apple has been reported (Beresford et al 2013). It is suggested that mycelial growth tests at 2 mg/litre may be a useful tool to screen single spore isolates quickly for potential carbendazim resistance development in future monitoring.…”
Section: Discussionmentioning
confidence: 99%